Analisis Penguatan Pendidikan Karakter Peserta Didik Melalui Kegiatan Ekstrakurikuler Tahfidz Al Qur’an Pada Siswa SD Muhammadiyah 1 Trenggalek - Fitrianingsih, Rizka Ayu; Janattaka, Nugrananda (Universitas Nusantara PGRI Kediri, 2020)
The pupose of this study is to describe the implementation of tahfidz al qur’an extracurricular activities, to descibe the character formation of students through tahfidz al qur’an extracurricular activities, to describe the impact of tahfidz al qur’an extracurricular activities on strengthening student character education. This research method includes the type of descriptive qualitative research. Data collection techniques used in the form of observation, using frank observation or disguised, this observation, observation made on students participating in tahfidz al qur’an extracurricular activities namely class 3 with a total of 36 students, and grades 4 and 5 were 37 students, interviews, intreviews, by looking for information on (principals, class teachers, and coaches of tahfidz al qur’an) and documentation studies. The data analysis technique uses interactive data analysis models, with the technique of checking the validity of the data using triangulation. The results of his research were the implementation of tahfidz al qur’an extracurricular activities which were attended by all students in grades 3, 4, and 5 with a total of 73 students, which would later be divided into groups according to the schedule made bye the school. Extracurricular activities as a forum for the formation of positive character toward students. Through the extracurricular activities of tahfidz al qur’an students are able to develop themselves, sharpen hidden talent in themselves, and love the qur’an to be memotized with melodious recitations to be heard, and able to become individuals who have good character and confidence. The results of this study can be used as insight to the school to always motivate students to be active in following the tahfidz al qur’an extracurricular activities so that the results of these activities can produce the best young cadres and graduates from the Muhammadiyah 1 Elementary School in Trenggalek.